Sulfide tolerance of juvenile tilapia (Orecromis mossambicus) in seawater. - Diaz, Ma. Maita F. (1996.)
The sulfide tolerance of juvenile tilapia Oreochromis masambicus was determined in terms of survival at different sulfide concentrations and different time periods. The lethal concentration for 50 of the fish at 4 h is 77 uM or 4.6 uM total sulfide and 61 uM or 3.7 total sulfide at 48 and 96 h. A flow-through glass aquaria system was used in the tolerance tests. No fish died in the controls and the fish could survive sulfide of only up to 38 uM total sulfide for 96 h. The low tolerance of tilapia to sulfide could possibly explain fish kills in brackishwater ponds. Occurences of high sulfide concentrations in the ponds could be toxic and detrimental to fish health.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Tilapia; Orecromis mossambicus -- Seawater